2017
DOI: 10.1253/circj.cj-16-1105
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mitral Annular Displacement on Left Ventricular Diastolic Function Improvement After Transcatheter Aortic Valve Implantation

Abstract: less attention than LV systolic function. [4][5][6] Movement of the mitral annulus towards the LV apex, which is referred to as mitral annular displacement (MAD), has been demonstrated as a result of the contraction of longitudinally oriented fibers across the LV wall. 7 Recent studies investigating the LV remodeling process induced by AS consistently indicated the importance of early histological changes in endocardial tissue such as interstitial fibrosis. 8-11 MAD may reflect histological changes in endocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…To a smaller extent, age might reduce relaxation properties in higher age groups, however, most of the diastolic parameters were not different between the two age groups ≥ 80 and <80 years in the present study. Even though the present study represents an older patient population with higher degree of AS compared to Steines and other younger study populations (2,7,19,21), we found a similar reduction of e´. Our results stress the predominance of factors other than age like LV hypertrophy, changed LV stiffness and increased afterload as the main reasons for decreased relaxation properties in AS patients.…”
Section: Diastolic Dysfunction In Aortic Stenosis Hemodynamic Considerationssupporting
confidence: 65%
See 3 more Smart Citations
“…To a smaller extent, age might reduce relaxation properties in higher age groups, however, most of the diastolic parameters were not different between the two age groups ≥ 80 and <80 years in the present study. Even though the present study represents an older patient population with higher degree of AS compared to Steines and other younger study populations (2,7,19,21), we found a similar reduction of e´. Our results stress the predominance of factors other than age like LV hypertrophy, changed LV stiffness and increased afterload as the main reasons for decreased relaxation properties in AS patients.…”
Section: Diastolic Dysfunction In Aortic Stenosis Hemodynamic Considerationssupporting
confidence: 65%
“…Even though e´ increases after TAVR/SAVR (7,19,(21)(22)(23), average e´ stayed lower than 10 cm/s in 90% of postoperative AS patients, indicating persistent impaired relaxation also after afterload reduction with AVR. Postoperatively, relaxation velocities in the lateral but not septal wall were signi cantly higher than pre-operative values, suggesting regionally inhomogeneous response to reduced afterload.…”
Section: Changes Of Diastolic Properties After Tavr/savrmentioning
confidence: 93%
See 2 more Smart Citations
“…Results of our study and previous investigations [ 5 , 20 , 22 ] on diastolic parameters in AS, indicate that most AS LVs predominantly display signs of impaired relaxation. This is reflected by low e′, which increases after TAVR/SAVR, though without complete normalization [ 10 , 23 ].…”
Section: Discussionmentioning
confidence: 99%